Factors influencing the employability of applicants in Tacloban City who graduated during the COVID-19 pandemic - Larraga, Jaren Kirby M.; Dacuyan, Flordeliz B.; Lobina, Vince Terry M.; Lucero, Gerardo III T. (2023)
This research study investigated the factors influencing the employability of applicants in Tacloban City who graduated during the COVID-19 pandemic. The study used a quantitative research design with a purposive sampling method, involving 60 respondents consisting of employers, managers, and human resource professionals from Tacloban City, Leyte. The study analyzed demographic profiles, skill sets, time spent on online learning, and internship experiences of applicants. The findings indicated that employers and human resource professionals show minimal consideration for demographic factors such as age, gender, and marital status when evaluating these applicants. Instead, employers prioritize specific skill sets, including technical competencies such as proficiency in Microsoft Office and technical writing, as well as discipline-related skills like professionalism and customer relationship management. Soft skills such as time management, decision-making, and multitasking are also valued. Interestingly, the duration of online learning during the pandemic does not significantly impact employability, with most employers not distinguishing between applicants who underwent online learning and those who did not. However, internship experience holds importance, with employers expressing a preference for candidates who have completed internships during the pandemic, particularly those with onsite experience. These findings provide valuable insights for students, highlighting the importance of developing relevant skill sets to enhance their employability during and post-pandemic. Future researchers can expand on these findings by considering the experiences and expectations of applicants, providing deeper insights into the dynamics of employability and guiding evidence-based decision-making.
Undergraduate thesis (B.S. Management) -- University of the Philippines, Tacloban.